Proposição de estratégias para controle profilático e terapêutico da encefalite autoimune experimental baseadas no efeito imunorregulador da hsp65 - Pezavento, Sofia Fernanda Gonçalves Zorzella [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
This project was mainly based on the immunoregulatory property of the mycobacterial hsp65. The proposal of this work was to evaluate if a DNA vaccine containing the hsp65 mycobacterial gene (pVAXhsp65) could be used as a prophylactic or therapeutic strategy to control experimental autoimmune encephalomyelitis (EAE) development. In the first part of this investigation we demonstrated that mice previously vaccinated with pVAXhsp65 lost less body weight and presented lower clinical score. Clinical improvement was associated with lower production of IL-10 by spleen cell cultures stimulated with MOG or ConA. Comparative histopathological analysis revealed less inflammatory process in the lumbar spinal cord of previously vaccinated mice in comparison to EAE control group. The second approach was designed to evaluate the possible therapeutic effect of pVAXhsp65 on EAE development. Even though this vaccine was immunogenic for mice with EAE and also able to downmodulate the induction of cytokines by MOG, it was not able to decrease the clinical severity of the disease. Vaccination did not decrease intensity of the inflammatory process neither the frequency of regulatory T cells (Tregs) in the central nervous system (CNS). Finally, we investigated the contribution of the peripheral and local IL-17 production to acute and chronic EAE stages. Mice submitted to EAE induction presented an initial acute phase characterized by accentuated weight loss and high clinical score, followed by a partial recovery when the animals reached normal body weight and smaller clinical scores. Spleen cells stimulated with MOG produced significantly higher levels of IFN-g during the acute period whereas similar IL-17 levels were produced during both Abstract disease stages. CNS infiltrating cells stimulated with MOG produced similar amounts of IFN-g but IL-17 was produced only at the acute phase of EAE. The percentage of Foxp3+ Treg cells, at the spleen and the CNS, was...

Este projeto foi baseado na propriedade imunorreguladora da hsp65 micobacteriana. A proposta geral foi avaliar se a vacina gênica contendo o gene da hsp65 do Mycobacterium leprae (pVAXhsp65) pode ser utilizada como estratégia profilática ou terapêutica na encefalite autoimune experimental (EAE). Na primeira etapa desta investigação constatamos que camundongos previamente imunizados com pVAXhsp65 perderam menos peso e apresentaram sintomatologia clínica mais branda. Essa melhora clínica esteve associada com redução da produção de IL-10 por células esplênicas estimuladas in vitro com MOG ou ConA. A análise histopatológica revelou redução do processo inflamatório na medula lombar dos animais previamente vacinados em comparação com o grupo controle EAE. Na segunda etapa avaliamos o efeito terapêutico de 4 doses de pVAXhsp65 no desenvolvimento da EAE. A vacina foi capaz de induzir resposta imune específica para hsp65 em camundongos com EAE, o que foi constatado pela produção de IFN-g e IL- 10. Além disso, a terapia modulou a imunidade específica para MOG reduzindo a produção de IFN-g, IL-6 e IL-17 por células esplênicas. Essa modulação não foi, entretanto, capaz de alterar o decurso clínico da doença. O processo inflamatório no sistema nervoso central (SNC) e a frequência de células T reguladoras (Tregs) na periferia e no SNC também não foram alterados pelo tratamento. Na última etapa desse projeto avaliamos mais detalhadamente a participação da IL-17 no decurso clínico da EAE. Na fase aguda (19º dia) foram observados perda acentuada de peso e elevado escore clínico (média de 2,75) enquanto que na fase crônica os animais recuperaram o peso perdido e o escore clínico se estabilizou em torno de 1,5. A produção de citocinas por órgãos linfoides secundários caracterizou-se por níveis elevados de IFN-g na fase aguda e de IL-17 na fase crônica. Já os linfócitos infiltrantes do SNC estimulados in...
Keywords: Imunologia; Vacinas; Encefalite - Tratamento; Cérebro - Doenças - Tratamento; Immunology